Implementation of Physiological Biology-Based Triage Learning to Improve The Accuracy of Emergency Patient Management By Students - Anto, Ambo; Susiati, Asih Luklu; Rismanudin, Rismanudin; Fony, Fony (Biology Teaching and Learning, 2024)
Abstract. This study aimed to analyze the effect of physiology-based triage learning implementation on the accuracy of emergency patient management by professional nursing students. Using a quasi-experimental pre-test and post-test design without a control group, 38 nursing students from Universitas Famika participated in an intervention involving simulation cases grounded in physiological concepts. Data were collected through physiology comprehension tests and triage accuracy assessments. The results showed significant improvements in both physiology understanding scores (from 64.13 to 79.05) and triage accuracy scores (from 60.74 to 82.39), with p-values < 0.001. Post-intervention distribution indicated that most students shifted into the “accurate” and “highly accurate” triage categories. These findings suggest that integrating physiological biology into triage education effectively enhances students’ clinical reasoning and decision-making accuracy in emergency care situations.Key words: case-based learning, clinical accuracy, nursing education, physiology, physiology, triage